Petty Cash Accounting Analysis on CV Min Java Farm - Zulhendra Zulhendra; Reski Nofrialdi (DINASTI RESEARCH, 2022)
The purpose of this study was to determine the management and accounting treatment of petty cash on CV. Min Java Farm. This research is located at Bukit Apit, Kenagarian Sungai Talang, Guguak District, 50 City Regency, West Sumatra. This research was conducted by direct observation using interview and documentation techniques. The data analysis technique used in this study is descriptive qualitative, the results of this study show the results of the petty cash accounting analysis are going well and in accordance with the applicable PSAK, in addition to the transaction process for disbursing petty cash funds, using petty cash funds, and replenishing cash funds. Minor activities have been carried out with the use of documents and in accordance with established procedures